Navigating the Complexities of ESG Integration: Challenges, Opportunities and Path to Sustainable Corporate Development - Gao, Huiping; Tan, Seng Teck; Syriac, Nellikunnel (INTI International University, 2024)
This study focuses on the practical application of the Environmental, Social, and Governance (ESG) framework and examines its role in promoting corporate sustainability and fulfilling social responsibilities. Through an analysis of theoretical frameworks, literature, and case studies, the paper highlights the major challenges ESG frameworks face in corporate operations, including stakeholder conflicts, short-term financial pressures, policy resistance, and inconsistent quantitative standards. Despite the significant achievements of ESG frameworks in enhancing brand reputation, attracting investors, and guiding sustainable development, the research also identifies issues such as "greenwashing," which undermine their overall credibility and effectiveness. The study suggests that companies must deeply integrate ESG principles with the United Nations Sustainable Development Goals (SDGs), leveraging innovation and improving transparency to transform social responsibility into competitive advantages, thereby driving the global economy's green transition and sustainable development.